CATEGORIES OF PHYLOSOPHY IN INVESTIGATION OF PROPERTY - A. I. Vankevich (Наука и техника)
Property in production goods in economics is characterized from various ideological and cognitive points. The paper considers categories of materialist dialectics, analysis and synthesis, internal contradiction, conflict of opposites, ascent principles from abstract to concrete, historical and logical principles as the most important forms of thinking in cognition of processes concerning origin, formation and developed state of property in production goods.